Another case of 'same bed, different dreams'? Assessing divergence and multidimensionality in energy evaluations and implications for interdisciplinary research and energy management. (2015) - Nippa, Michael; Lee, Roh Pin
This study represents an in-depth effort to investigate divergence and multidimensionality in energy evaluations. Two forms of evaluative responses are investigated, namely affective energy perception and cognitive energy beliefs. Specifically, we assessed the role of education background and gender in influencing affective energy perception. Additionally, we examined for multidimensionality in cognitive energy beliefs, 399 university students from engineering and business disciplines and students from a non-university institution participated in a survey in 2011 to assess their affective energy perception as well as their beliefs of social, economic and environmental harms and benefits associated with diverse energy sources. Findings relating to nuclear and fossil-based (i.e., coal, natural gas and oil) energy sources are presented in this paper. Analyses indicate significant divergence in affect towards nuclear energy between young adults from different education disciplines and levels. Findings are also suggestive of an additive effect of education background and gender on energy perception. Furthermore, participants not only significantly differentiated between social, economic and environmental dimensions in their energy beliefs, they also exhibited a general confounding of harm and benefit beliefs. Implications for energy management and interdisciplinary energy research collaborations are discussed.